TANGGUNG JAWAB ORANG TUA TERHADAP ANAK SETELAH PERCERAIAN (STUDI KASUS : DI PENGADILAN AGAMA TALU - Habi bullah (Menara Ilmu, 2018)
If also associated with the material needs / children who live in a family that both parentshave divorced, the growth and development of children would have a serious obstacle if thematerial / physical needs of children in the form of maintenance and education costs of childrento adulthood there is no clarity. the formulation of the problem in this study is: what is theparent's responsibility to the child after the divorce, how does the judge judge decide upon theparent's responsibility for the child after the divorce and how the legal consequences for theparent who does not carry out their obligations to the child after the divorce. This study is anempirical legal research or sociological juridical method. This research uses descriptiveapproach (descriptive approach). This research was conducted in Talu Religious Court atSimpang Empat. Population in this research is judge of Talu religion which determined bypurposive sampling. The number of samples of this study as many as 3 people. Data type isprimary data and secondary data. The tool used to collect primary data in this research isinterview technique (interview) with interview guide (interview guide). The data analysis isqualitative analysis. The results show that divorce will not eliminate or abort parental obligationsto their children. The breakup of marriage between the applicant and the defendant, both are stillobliged to provide maintenance (hadhanah) and maintenance to their children. As for the judge'sconsideration in deciding the divorce decision in the Religious Court of Talu regarding thedivorce divorce Number: 0191 / Pdt.G / 2015 / PA.TALU considers two things, namely the lawand the consideration of sitting his case or event. Because divorce happens on the basis ofarguments and disputes that can not be reconciled again. The legal consequences for parents whodo not carry out their obligations to the child can be pursued two things: First, against the partycharged the cost of living, if not perform the obligations can be requested execution. Second, tothe holder of the foster care, if not perform the obligations it can be requested for the revocationof power of foster care. However, revocation of the power of foster does not make the obligationas a parent to his son fell.